Efektivitas Penerapan Pola Tabungan dalam Meningkatkan Minat Konsumen pada Penjualan Ritel Hewan Qurban - Nurdin, Nurdin; Hadi Sutrisno; Lesmana, Asep Surya; Sari, Yuliya; Umar Anas (Yayasan Literasi Sains Indonesia, 2025)
Qurban is an obligation for financially capable Muslims, yet financial constraints often hinder participation, particularly among middle-income groups. The qurban savings scheme serves as an innovative solution through phased financial planning. This study analyzes the effectiveness of the qurban savings system in boosting retail qurban animal consumers’ interest, while identifying preferences, driving factors, and its impact on pricing and animal availability. Conducted from December 2024 to April 2025, the research employs a qualitative approach via questionnaires (78 respondents) and interviews. Results indicate 85% of respondents (aligned with findings) benefited from deposit flexibility and reduced financial pressure. Key participation factors include trust in institutions (67%), ease of digital payment (58%), and animal quality assurance (72%). A total of 89% of female respondents prioritized QR Code-based vaccine certification. However, 49% faced difficulties securing animals 7 days before Eid, and 61% of rural participants discontinued savings due to transparency issues. Dependence on intermediaries by 88% of non-Jabodetabek breeders inflated price margins and inefficiencies. The study recommends integrating digital technology and blockchain-based traceability, alongside multi-stakeholder collaboration to establish inclusive operational standards. Taklim assembly-based financial literacy is crucial to enhance vulnerable groups’ participation.